Intimate partner violence in pregnancy: planning and pregnancy monitoring - Moreira, Rosa Maria Santos (2016)
The intimate partner violence (IPV) in pregnancy results in risk factors with an impact on maternal and fetal health. There is a tendency to unwanted pregnancies, unplanned and poor adherence to health services, increasing the risk of complications during pregnancy. The aim is describe the prevalence rates of IPV during pregnancy in the Central Region of Portugal and analyse their association with pregnancy planning and frequency of prenatal consultations. There was prevalence of IPV during pregnancy with a significant association to pregnancy planning. Although most women have attended prenatal consultations in the last pregnancy, the late start is associated with the probability of frequency of some type of IPV.